The Influence of Organizational Culture on Employee Engagement: The Role of Organizational Commitment As An Intervening Variable - Agus Siswanto (Greenation Research & Yayasan Global Resarch National, 2023)
The purpose of this paper is to determine the influence of Organizational Culture on employee engagement with organizational commitment as an intervening variable. This research used a quantitative approach to reveal the relationship between research variables with Structural Equation Modeling (PLS-SEM) as a data analysis tool. The findings of this research are Organizational Culture has a positive and significant influence on employee engagement. Organizational commitment has a positive and significant influence on mediating Organizational Culture to employee engagement. This research provides a new perspective on Human Resource Management with KSPPS BMT UGT Nusantara as the research object.